Influ??ncia da mobiliza????o mandibular inespec??fica sobre o movimento mandibular de indiv??duos com disfun????o temporomandibular: ensaio cl??nico, aleatorizado, placebo-controlado e cego - Amaral, Ana Paula (2016)
Temporomandibular dysfunction is defined as a group of heterogeneous alterations that affect the temporomandibular joint, affecting important functional and anatomical elements, characterizing itself as a complex and multifactorial disease. His doctoral thesis was divided into four studies with the following objectives: Article 1 (protocol) and Article 4: to evaluate the influence of non-specific mandibular mobilization on mandibular opening movements and lateral excursions in women with TMD by means of pachymetry and the three-dimensional kinematic analysis of movement, as well as assessing pain intensity, functionality and quality of life; Article 2: identify if manual therapy is effective in treating TMD, as well as assess the accuracy of tools that are used to evaluate the rehabilitation of patients with TMD; Article 3: investigate the immediate effect of nonspecific mandibular mobilization on the range of motion in individuals with temporomandibular dysfunction. Thus we obtained as a result and conclusion: Article 2: manual therapy is effective in the treatment of TMD mainly in the reduction of muscular pain and to improve the ROM. The visual analogue scale (VAS) and clinical evaluation using RDC / TMD are the most used tools to evaluate the effects of Manual Therapy; Article 3: Nonspecific mandibular mobilization led to an immediate increase in maximal vertical mandibular movement, as well as increases in right and left lateral excursion in individuals with and without TMD; Article 4: Non-specific mandibular mobilization decreases pain intensity and influences the clinical improvement of the mandibular opening amplitude measured by pachymetry, but does not influence the functionality, quality of life and trajectory of the mandibular movements of patients with temporomandibular dysfunction.